Optimization of extraction and microencapsulation of bioactive compounds from red grape (Vitis vinifera L.) pomace - Boonchu T. (2014)
Grape (Vitis vinifera L.) pomace constitutes a promising source of phenolic compounds, gallic acid, flavan-3-ols, flavonoids, stilbene and anthocyanins that are beneficial for human health. The objectives of this study were to optimize the extraction and microencapsulation of red grape pomace. Central composite designs with two factors were conducted for optimization using response surface methodology. The temperature (45-85 °C), and the time (2-8 h) were designed for the extraction. The results indicated that the extraction temperature and time introduced the increasing the extraction yield, total phenolic content, anthocyanin and resveratrol, but the long extraction time reduced the tannin content. The results showed that the optimize condition was the extraction at 80 ± 1 °C for 2 h 53 min. This provided the highest content of polyphenolic compounds. The next experiment was microencapsulation of the extract which studied the amounts of maltodextrin (7-28 % w/v) and carboxymethylcellulose (CMC) (0-1.4 % w/v). The results showed that the optimized microencapsulation used 10.21 % w/v maltodextrin and 0.21 % w/v CMC to maximize all polyphenolic compounds, and also to minimize bitterness and astringency. This study illustrated that the optimal conditions for extraction and microencapsulation of the red grape extract have a high potential to produce functional ingredients. © 2013 Association of Food Scientists & Technologists (India).